AUDIT COMMITTEE AS A MODERATOR ON THE RELATIONSHIP BETWEEN DIVERSITYINBOARD AND ENVIRONMENTAL REPORTING OF LISTED MANUFACTURING COMPANIES IN NIGERIA - Salvation Joshua Selven; Timkat Nanmak Peter; Gong Chai Deme; Joshua Rinarimam (Gusau Journal of Accounting and Finance, 2025)
Corporate environmental practices are facing more and more scrutiny from stakeholders as a result of growing ecological concerns that affect not just local communities but the planet as a whole. To this end, this paper examines the moderating role of audit committees on the relationship between diversity-in-board and environmental reporting of Listed Manufacturing Companies in Nigeria (LMCN). The paper employed an ex-post facto research design and data collected from annual reports of thirty-six LMCN were analyzed using descriptive statistics and linear multiple regression techniques. Findings suggest that while diversity-in-board positively influenced environmental reporting, this effect became statistically significant when moderated by the audit committee. This underscores the importance of audit committee crucial role as a moderator in influences that impact of diversity-in-board and ensures adequate disclosure of environmental information in the annual reports of listed manufacturing companies in Nigeria. The study recommends among others that Financial Reporting Council (FRC) of Nigeria should no longer allow environmental disclosure in Nigeria to be voluntary, but make it compulsory using ISO 14031 reporting guideline as a common standard among listed manufacturing firms in Nigeria for the purpose of attaining detailed environmental disclosures and easy comparison of such disclosures among firms. Also, encourage regulators to regularly review corporate governance codes to strengthen diversity provisions for more credible stakeholder reporting. Additionally, manufacturing firms should focus on boosting the effectiveness of their audit committees to enhance environmental stewardship, which will in turn improve corporate brand image and reputation.